Modern diagnostic approaches for early detection of antiphospholipid syndrome - Zhanna Arapbaevna, Kulanchiyeva; Ardak, Ayazbekov; Gulbanu Abzhanovna, Arynova; Anara Bahitkerevna, Daniyarova; Alma Uringalievna, Baltayeva; Elmira Izbasarovna, Kussaiynova; Ainura Malikovna, Dauletbakova; Akbota Erbolovna, Danagulova (AVFT – Archivos Venezolanos de Farmacología y Terapéutica, 2021)
Currently, Antiphospholipid syndrome is a multidisciplinary problem, as it is one of the causes of death and disability of patients. Cardiovascular diseases occupy a leading position among the causes of mortality. The reproductive function of women determines not only the quality of their life and offspring, but also the health and quality of life of the nation. Based on a comprehensive assessment of the results of clinical, laboratory and instrumental studies, general and distinctive features of the primary and secondary Antiphospholipid syndrome are shown, on which their differential diagnosis is based. The use of a multiplex test - immunoblotting will reliably reveal the primary Antiphospholipid syndrome